The Western Gulf of Corinth (Greece) 2020–2021 Seismic Crisis and Cascading Events: First Results from the Corinth Rift Laboratory Network - George Kaviris; Panagiotis Elias; Vasilis Kapetanidis; Anna Serpetsidaki; Andreas Karakonstantis; Vladimír Plicka; Louis De Barros; Efthimios Sokos; Ioannis Kassaras; Vassilis Sakkas; Ioannis Spingos; Sophie Lambotte; et al. (The Seismic Record, 2021)
We investigate a seismic crisis that occurred in the western Gulf of Corinth (Greece) between December 2020 and February 2021. This area is the main focus of the Corinth Rift Laboratory (CRL) network, and has been closely monitored with local seismological and geodetic networks for 20 yr. The 2020–2021 seismic crisis evolved in three stages: It started with an Mw 4.6 event near the northern shore of the Gulf, opposite of Aigion, then migrated eastward toward Trizonia Island after an Mw 5.0 event, and eventually culminated with an Mw 5.3 event, ∼3 km northeast of the Psathopyrgos fault. Aftershocks gradually migrated westward, triggering another cluster near the junction with the Rion–Patras fault. Moment tensor inversion revealed mainly normal faulting; however, some strike-slip mechanisms also exist, composing a complex tectonic regime in this region dominated by east–west normal faults. We employ seismic and geodetic observations to constrain the geometry and kinematics of the structures that hosted the major events. We discuss possible triggering mechanisms of the second and third stages of the sequence, including fluids migration and aseismic creep, and propose potential implications of the Mw 5.3 mainshock for the seismic hazard of the region.